Income Tax Cut and Firm Tax Avoidance - Saputra, Ruri; Yulianti, Yulianti (E-Jurnal Akuntansi, 2023)
This study aims to examine the impact of Indonesian corporate income tax rate reduction on public companies’ tax avoidance. This study utilizes a quasi-experimental design with the difference-in-differences (DID) method to isolate the effect of corporate income tax rates changes on corporate tax avoidance behavior. Firms’ ownership structure is used to separate firms that are more likely to be affected by the tax law changes, thus representing the treatment group in the DID setting.  Utilizing a sample of public companies listed on the Indonesia Stock Exchange in the 2019 and 2020 periods, this study finds that in the year preceding the tax rate reduction, firms with greater institutional ownership exercise higher tax avoidance compared to other firms. The differences, however, are not statistically significant, which may be caused by the short timespan between the policy announcement and tax filing period, limiting the time available for firms to adjust their tax avoidance behavior. Keywords: Tax Cut, Tax Avoidance, Institutional Investor